Bacterial anoxygenic photosynthesis on plant leaf surfaces - Atamna-Ismaeel, Nof; Finkel, Omri; Glaser, Fabian; von Mering, Christian; Vorholt, Julia A; Koblížek, Michal; Belkin, Shimshon; Béjà, Oded (Environmental microbiology reports, 2012)
The aerial surface of plants, the phyllosphere, is colonized by numerous bacteria displaying diverse metabolic properties that enable their survival in this specific habitat. Recently, we reported on the presence of microbial rhodopsin harbouring bacteria on the top of leaf surfaces. Here, we report on the presence of additional bacterial populations capable of harvesting light as a means of supplementing their metabolic requirements. An analysis of six phyllosphere metagenomes revealed the presence of a diverse community of anoxygenic phototrophic bacteria, including the previously reported methylobacteria, as well as other known and unknown phototrophs. The presence of anoxygenic phototrophic bacteria was also confirmed in situ by infrared epifluorescence microscopy. The microscopic enumeration correlated with estimates based on metagenomic analyses, confirming both the presence and high abundance of these microorganisms in the phyllosphere. Our data suggest that the phyllosphere contains a phylogenetically diverse assemblage of phototrophic species, including some yet undescribed bacterial clades that appear to be phyllosphere-unique.